Gisela Procházka-Eisl. Enverīzāde Sa‘dullāh Enverī Efendi’s “Treatise on Austria”: Risāle-i Avusturya. - Benli, Şeyma (Zemin, 2024)
Kitabiyat: Gisela Procházka-Eisl. Enverīzāde Sa‘dullāh Enverī Efendi’s “Treatise on Austria”: Risāle-i Avusturya. Berlin: EB-Verlag, 2022. 202 p., ISBN: 9783868934076.